Approach on Applications of Random High Data Flows Concerning the Architecture of Computer Networks - Gaitan, A. M.; Popa, V.; Gaitan, V G.; Hrebenciuc, F. A. (Elektronika ir Elektrotechnika, 2010)
The Radio Frequency Identification (RFID) technology has reached our lives during the last years, by means of providing new alternatives as comparing to other identification methods, such as bar codes. In order to transmit the information stored on tags, the RFID technology uses wireless communication. It also creates flexible and scalable identification systems. The RFID technology has started to be used to various fields, such as supply chain management, track and trace of animals and many other applications, in a contactless manner of tracking the entities. This paper proposes a revolutionary identification system. By the help of connecting the RFID devices within high complex networks, this system will offer flexibility and scalability as concerns the management of random high data flows.